Growth factor choice is critical for successful functionalization of nanoparticles - Pinkernelle, Josephine; raffa, vittoria; calatayud, maria p.; goya, gerado f.; riggio, cristina; Keilhoff, Gerburg (Frontiers in Neuroscience, 2015)
Nanoparticles (NPs) show new characteristics compared to the corresponding bulk material. These nanoscale properties make them interesting for various applications in biomedicine and life sciences. One field of application is the use of magnetic NPs to support regeneration in the nervous system. Drug delivery requires a functionalization of NPs with bio-functional molecules. In our study, we functionalized self-made PEI-coated iron oxide NPs with nerve growth factor (NGF) and glial cell-line derived neurotrophic factor (GDNF). Next, we tested the bio-functionality of NGF in a rat pheochromocytoma cell line (PC12) and the bio-functionality of GDNF in an organotypic spinal cord culture. Covalent binding of NGF to PEI-NPs impaired bio-functionality of NGF, but non-covalent approach differentiated PC12 cells reliably. Non-covalent binding of GDNF showed a satisfying bio-functionality of GDNF:PEI-NPs, but turned out to be instable in conjugation to the PEI-NPs. Taken together, our study showed the importance of assessing bio-functionality and binding stability of functionalized growth factors using proper biological models. It also shows that successful functionalization of magnetic NPs with growth factors is dependent on the used binding chemistry and that it is hardly predictable. For use as therapeutics, functionalization strategies have to be reproducible and future studies are needed.